A comparative analysis of sinonasal and salivary gland mucoepidermoid carcinoma using population‐based data. Issue 1 (20th October 2014) - Patel, Tapan D.; Vázquez, Alejandro; Patel, Dhruv M.; Baredes, Soly; Eloy, Jean Anderson
<x xml:space="preserve">Abstract</x> Background Mucoepidermoid carcinoma (MEC) is the most common salivary gland (SG) malignancy. Primary sinonasal MEC (SN‐MEC) is rare. This study analyzes the demographic, clinicopathologic, and survival characteristics of SN‐MEC and establishes comparisons with primary major SG‐MEC. Methods The Surveillance, Epidemiology, and End Results (SEER) database (1973 to 2010) was queried for SN‐MEC (149 cases) and SG‐MEC (4234 cases). Data were analyzed comparatively with respect to various demographic and clinicopathologic factors. Survival was analyzed using the Kaplan‐Meier and Cox proportional hazards models. Results Mean ± standard deviation (SD) age at diagnosis for SN‐MEC was 58.6 ± 16.6 years. High histologic grade (ie, grades III and IV) at the time of diagnosis was more common among SN‐MEC than SG‐MEC (42.3% vs 25.5%, p < 0.0001). Overall 5‐year disease‐specific survival (DSS) was 61.7% for SN‐MEC and 84.1% for SG‐MEC (p < 0.001). For SN‐MEC, factors associated with poor prognosis were age (75+ years; hazard ratio [HR], 3.38; 95% confidence interval [CI], 1.25 to 9.51), higher tumor grade (grade III and IV; HR, 3.62; 95% CI, 1.75 to 8.22), larger tumor size (>4 cm; HR, 8.36, 95% CI, 1.59 to 153.74), and primary tumor site (ethmoid sinus; HR, 2.95; 95% CI, 1.28 to 6.23) (all p < 0.05). Survival was better among those treated with surgery (with [64.4% survival] or without [81.3% survival] adjuvant radiation therapy) than those treated with primary radiation therapy alone (25.6% survival) (p < 0.05). Conclusion This report represents the largest series of SN‐MEC to date. Although SN‐MEC and SG‐MEC share a common histology, there are important clinical differences between the 2 conditions.